Mediators of Change in Insulin Resistance with Weight-loss and Exercise Through the use of HOMA-IR - Hiller, Kayleigh M (East Carolina University, 2021)
Purpose: It has been evidenced that the prevalence of obesity and type 2 diabetes (T2D) have significantly increased in the United States over the past two decades. However, previous studies have demonstrated that a reduction in body weight, fat mass, and increase in aerobic exercise have the potential to reduce T2D risk. While fasting glucose and insulin levels indicate, in some respect, the T2D risk of an individual, the homeostatic model assessment of insulin resistance (HOMA-IR) specifically estimates the level of insulin resistance of an individual. The primary purpose of this study was to understand the mediators of response for HOMA-IR following a 10-week, combined aerobic exercise and OPTIFAST weight loss intervention. The mediators of interest were changes in body weight, fat mass, lean mass, and maximal oxygen consumption (VO2 max). Methods: The present study is a secondary analysis of the Prescribed Exercise to Reduce Recidivism After Weight Loss pilot (PREVAIL-P) study that took place at East Carolina University. The intervention consisted of moderate-intensity aerobic exercise training on a treadmill combined with the OPTIFAST weight loss program. The study sample consisted of 36 individuals with a mean age of 47 - 11 years, characterized as either overweight or obese. The OPTIFAST program supplemented with exercise allowed participants to achieve the [less-than or equal to]7%weight-loss goal by the end of the 10 weeks. Clinical measurements were taken at baseline and week 10 of the study to assess for changes following the intervention using paired t-tests. Measurements consisted of body weight, waist circumference, body composition, absolute and relative VO2 max, and the level of insulin resistance by calculating HOMA-IR (Fasting Plasma Insulin uIU/mL x Fasting Plasma Glucose mg/dL)/405). Body weight was measured using a physician beam scale and body composition was assessed using Dual-Energy X-Ray Absorptiometry (DEXA). Cardiorespiratory fitness (absolute and relative VO2 max) was assessed using a modified Balke treadmill protocol with indirect calorimetry. Fasting blood glucose and insulin samples were taken on site and sent to LabCorp for analysis. The HOMA-IR scores were calculated using Microsoft Excel and the IBM® SPSS statistics program. Results: Following the intervention, the 36 subjects achieved a mean weight loss of 9.3 ± 2.9%. Compared to baseline, we observed a significant decrease in HOMA-IR, fasting insulin, and fasting glucose levels (all p[less-than]0.001). Similarly, we observed a significant decrease in outcome variables (i.e. body weight, waist circumference, BMI, lean mass, and fat mass) and a significant increase in relative VO2 max (all p[less-than]0.001). A Pearson Correlation assessed the changes in HOMA-IR with changes in body weight, fat mass, lean mass, and absolute VO2 which showed little significance as mediators of change. However, there was a significant negative correlation (r=-0.92, p[less-than]0.001) between baseline and follow-up HOMA-IR. Conclusion: The primary finding of the present study suggests that baseline HOMA-IR is the most important factor for predicting improvements in insulin resistance in the overweight and obese population following a combined OPTIFAST weight loss and aerobic exercise program. This suggests that overweight and obese adults with elevated levels of insulin resistance can especially benefit from this type of intervention.
Keywords: HOMA-IR; medically supervised clinically-significant weight-loss; supervised aerobic exercise; insulin resistance; Diabetes--Exercise therapy--United States; Aerobic exercises; Weight loss; Obesity--Treatment